Density‐Dependent Emission Colors from a Conformation‐Switching Chromophore in Polyurethanes. Issue 1 (23rd November 2021) - Wang, Junwei; Yan, Rui; Hu, Yaofang; Du, Guoshuai; Liao, Guanming; Yang, Huanzhi; Luo, Yunjun; Zheng, Xiaoyan; Chen, Yabin; Wang, Suning; Li, Xiaoyu
Abstract: Achieving full‐color emission from a single chromophore is not only highly desirable from practical considerations, but also greatly challenging for fundamental research. Herein, we demonstrated the density‐dependent emission colors from a single boron‐containing chromophore, from which multi‐color fluorescent polyurethanes were prepared as well. Originating from its switchable molecular conformations, the emission color of the chromophore was found to be governed by the packing density and strongly influenced by hydrogen bonding interactions. The chromophore was incorporated into polyurethanes to achieve full‐color emitting materials; the emission color was only dependent on the chromophore density and could be tuned via synthetic approach by controlling the compositions. The emission colors could also be modulated by physical approaches, including by swelling/deswelling process, compression under high pressure, and even blending the fluorescent polyurethane with non‐emitting ones. Abstract : Full‐color emission is achieved from a single fluorescent component by incorporating it into polyurethane matrices. Facilitated by the chemical structure of polyurethanes, the emission color could be modulated from blue to red by simply tuning the density of the chromophores, via either synthetic or physical approaches.